Wavelet estimation of the long memory parameter for Hermite polynomial of Gaussian processes∗∗∗. (28th November 2013) - Clausel, M.; Roueff, F.; Taqqu, M.S.; Tudor, C.
Abstract : We consider stationary processes with long memory which are non-Gaussian and represented as Hermite polynomials of a Gaussian process. We focus on the corresponding wavelet coefficients and study the asymptotic behavior of the sum of their squares since this sum is often used for estimating the long–memory parameter. We show that the limit is not Gaussian but can be expressed using the non-Gaussian Rosenblatt process defined as a Wiener–Itô integral of order 2. This happens even if the original process is defined through a Hermite polynomial of order higher than 2.